Gerakan 100 Sertifikasi Halal UMKM di Sulawesi Barat - Abbas, Wandi; Amin, Asma; Farhanuddin (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
MSMEs regarding halal labels is still not fully understood, so there is a need for socialization in the community regarding halal label information. Halal labels have been stipulated in the Halal Product Guarantee Law. The purpose of this community service activity is to assist West Sulawesi MSMEs in applying for and obtaining halal product certification for their MSMEs. The method of implementing the activity used is Socialization and assistance both directly and indirectly with participants. The results of the implementation of this activity are an increase in knowledge and understanding related to halal labels, in addition, the participants are also very active and enthusiastic in participating in counseling activities and understanding related to digital marketing strategies. With the increase in knowledge and understanding of participants about halal labels, it is hoped that it can have a positive impact, namely increasing public awareness of halal products and encouraging MSMEs to allow halal certification on the products they produce.